EFL Learners' Perceptions of Classroom Justice: Does Teacher Immediacy and Credibility Matter? - Sun, Ruiyun (Frontiers in Psychology, 2022)
Because learners’ perceptions of classroom justice are highly influential on their academic performance, recognizing personal and interpersonal factors that may modify these perceptions seems necessary. Notwithstanding this necessity, a scant number of inquiries have focused on the role of interpersonal factors such as credibility and immediacy in learners’ perceptions of classroom justice. In fact, the function of these factors has been overlooked by previous studies. Furthermore, no theoretical review has been performed in this area. To make a stride toward narrowing this lacuna, this theoretical review intends to clarify the role of two interpersonal factors, namely immediacy and credibility, in EFL learners’ perceptions of classroom justice. To accomplish this, the previous inquiries were meticulously reviewed. The findings of the review revealed that EFL learners’ perceptions of classroom justice can be drastically affected by teacher immediacy and credibility. The finding’s implications are also discussed in detail.